2022
DOI: 10.3390/vaccines10111867
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of an mRNA-Based COVID-19 Vaccine among Adolescents with Obesity or Liver Transplants

Abstract: There are limited data regarding the immunogenicity of mRNA-based SARS-CoV-2 vaccine BNT162b2 among immunosuppressed or obese adolescents. We evaluated the humoral immune response in adolescents with obesity and adolescent liver transplant recipients (LTRs) after receiving two BNT162b2 doses. Sixty-eight participants (44 males; mean age 14.9 ± 1.7 years), comprising 12 LTRs, 24 obese, and 32 healthy adolescents, were enrolled. Immunogenicity was evaluated by anti-SARS-CoV-2 spike protein immunoassay and surrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
8
2
Order By: Relevance
“…Previous reports demonstrated a lower immunogenic response in adolescents LT recipients compared to healthy controls, [20] and a booster vaccine might be required. [21] Although our study did not reveal any differences between severity, duration of symptoms, and incidence of long COVID-19 among patients with and without vaccination, we found that fever was less found in patients who Most children in this study received favipiravir for the treatment of COVID-19, according to the national treatment guidelines, [22] suggesting the consideration of favipiravir therapy among symptomatic children with immunosuppressed state. However, the efficacy of favipiravir is still debatable.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous reports demonstrated a lower immunogenic response in adolescents LT recipients compared to healthy controls, [20] and a booster vaccine might be required. [21] Although our study did not reveal any differences between severity, duration of symptoms, and incidence of long COVID-19 among patients with and without vaccination, we found that fever was less found in patients who Most children in this study received favipiravir for the treatment of COVID-19, according to the national treatment guidelines, [22] suggesting the consideration of favipiravir therapy among symptomatic children with immunosuppressed state. However, the efficacy of favipiravir is still debatable.…”
Section: Discussioncontrasting
confidence: 54%
“…Of these, 59 were excluded because they did not meet the eligibility criteria. Therefore, 15 studies were included in the review [ 11 , 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 12 selected studies [ 11 , 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], eight cohort studies [ 11 , 13 , 14 , 18 , 19 , 23 , 24 , 25 ] provided absolute values of antibody titers in an obese group and nonobese group, and three studies [ 11 , 13 , 25 ] offered baseline antibody titers. When compared with the nonobese groups, the antibody titers of the obese groups were lower [ 11 , 13 , 14 , 18 , 19 , 20 , 22 , 23 , 24 , 26 ]. However, two studies [ 21 , 25 ] suggested that obesity was not associated with antibody responses after two doses of ChAdOx1 nCoV-19 vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations